Decreased plasma ghrelin in male ALS patients is associated with poor prognosis. (April 2022) - Nagaoka, Utako; Shimizu, Toshio; Uchihara, Toshiki; Komori, Takashi; Hosoda, Hiroshi; Takahashi, Kazushi
Highlights: Among ALS, male had lower plasma ghrelin levels than female, but disease specificity is unknown. Low plasma ghrelin in male ALS was not associated with BMI, food intake, or physical dysfunction. Male ALS with low plasma ghrelin had significantly shorter survival times. Ghrelin levels are an independent predictor of survival among ALS patients. Ghrelin-positive cells may reduce in ALS with low plasma ghrelin. Abstract: Physiological changes including altered nutritional status influence disease progression and survival in patients with amyotrophic lateral sclerosis (ALS). Ghrelin affects the nutritional status by regulating appetite and energy expenditure, and also has neuroprotective effects. To investigate the association between ghrelin and ALS prognosis, we analyzed plasma acylated-ghrelin levels in 33 patients with ALS. Compared among ALS patients, male had lower plasma ghrelin levels than female, although disease specificity is unknown. ALS patients, especially male ALS patients, with low plasma ghrelin levels (<15 fmol/mL) had significantly shorter post-examination survival times than those with high plasma ghrelin levels (≥15 fmol/mL). Univariate and multivariate analyses revealed a significant effect of ghrelin levels on post-examination survival. Immunohistochemical study of autopsied stomach samples from 8 of 33 patients revealed that the population of ghrelin-positive cells tended to be reduced in the low-plasma ghrelin group than in the high-plasma ghrelin group. Our findings suggest that ghrelin levels are an independent predictor of survival in ALS, especially male ALS patients, and the ghrelin-positive cells may decrease in ALS with low plasma ghrelin. Thus, reduced ghrelin secretion may be associated with poor prognosis among patients with ALS.